Social determinants of health and glycemic control in persons with type 2 diabetes mellitus attending a tertiary hospital in Nepal: A cross-sectional study - Prava Adhikari; Aurawamon Sriyuktasuth; Warunee Phligbua (Belitung Nursing Journal, 2023)
Background: Diabetes mellitus (DM) is an emerging global public health challenge worldwide, including Nepal. Social determinants of health (SDOH) play a major role in glycemic control among persons with type 2 DM (T2DM). However, little is known about the association between SDOH and glycemic control among individuals with T2DM in Nepal. Objective: This study aimed to identify the level of glycemic control and SDOH associated with glycemic control among Nepalese with T2DM. Methods: This cross-sectional study was conducted at a tertiary hospital in Kathmandu, Nepal, among 135 Nepalese diagnosed with T2DM who attended follow-up appointments. Convenience sampling and inclusion criteria were utilized for participant selection. Data were collected from April to June 2021 using validated scales. Descriptive statistics, Chi-square test, and binary logistic regression were employed to analyze the data. Results: The mean age of the participants in this study was 53.84 (SD = 11.78) years, and the average monthly household income was 567.64 (SD = 362.30) USD. The majority of the participants (77.8%) were literate and had no health insurance coverage (73.3%). Approximately 64.4% of the participants showed suboptimal glycemic control indicated by glycated hemoglobin (HbA1c) ≥7%. The significant determinants of good glycemic control included monthly household income of  >850 USD (odds ratio  [OR] = 12.20, 95% confident interval [CI] = 1.76–84.61, p = 0.011) and 341–600 USD (OR = 7.64, 95% CI 1.35–42.98, p = 0.021), being literate (OR = 6.37, 95% CI = 1.65–24.49, p = 0.007), having health insurance (OR = 5.82, 95% CI = 1.49–22.65, p = 0.011), sufficient health literacy (OR = 3.46, 95% CI = 1.10–10.83, p = 0.03), and high (OR = 16.17, 95% CI = 2.36–110.67, p = 0.005)  and moderate (OR = 7.02, 95% CI = 1.26–39.07, p = 0.026) food availability, respectively. Conclusion: The study revealed suboptimal glycemic control in Nepalese with T2DM. This study presents essential social determinants of glycemic control in this population. Therefore, healthcare providers, particularly nurses, should pay more attention to assessing social determinants and provide targeted interventions to patients with T2DM who have low income, are illiterate, have no health insurance coverage, have insufficient health literacy, and have low resources for food availability.